Revitalization of Hindu Religious Education in Instilling Dharma Values in the Digital Era - I Ketut Sudarsana; Ni Gusti Ayu Agung Nerawati; Ni Wayan Sariani Binawati (International Journal of Social Learning (IJSL), 2025)
Hindu Religious Education plays a strategic role in shaping the character of students based on Dharma values, especially in the era of globalization and digitalization, which is prone to moral disorientation. This study aims to examine the strengthening of Hindu religious education through curriculum innovation, the utilization of information technology, and the integration of local wisdom values in the learning process. This study employs a qualitative approach, drawing on a literature review that examines Hindu sacred texts, character education literature, and recent research findings on pedagogical challenges in the digital era. The results of the study indicate that effective Hindu religious education must be dynamic and adaptive without abandoning Hindu spiritual roots. Teachers as agents of change need to master the use of digital technology such as audiovisual media, online learning platforms, and interactive learning resources. A contextual approach, through the exploration of the Hindu Nusantara tradition, also strengthens the relevance of learning. This study highlights the importance of revitalizing holistic Hindu education by integrating philosophical, pedagogical, and technological aspects to cultivate a generation of intelligent, noble, and spiritually inclined young Hindus.